The Protohistory of School Historiography of History of Art (18th and 19th Centuries): Epistemological Approaches and Socio-Educational Purposes Based on the Enlightenment Proposals and the Work of Manjarrés - López-Castelló, Raúl (REVISTA DE HISTORIOGRAFÍA (RevHisto), 2024)
In this study, we delve into the examination and systematization of some aspects of the protohistory of the History of Art as a school subject so that its change and continuity can be traced later in its proper school development. For this, we go back to the Enlightment and the teaching of History of Art in the Academies of Fine Arts, whose derived products will have a great influence on the conformation of a whole series of discourses, uses and practices that will become the definers of a school tradition. The article, thus, tries to integrate some of the previous studies that have dealt with the matter and delves into some of its reference sources, especially the manual by José de Manjarrés y Bofarull (1859) aimed at training future artists. The conclusion points to an incipient History of Art characterized by a teleological vision that tends to the canonization of certain contents, with a discourse built on the basis of certain ethnocentrisms.
Keywords: Historiography; History of Art; disciplinary code; Academies of Fine Arts; Manjarrés; teaching; epistemology; identities